Impact of DENV Genotypic Variation on Vaccine Efficacy and Cross-Neutralizing Antibody Responses: A Meta-Analysis - Utari Gusti Yulimdra; Dewi Anggraini; Fauzia Andrini Djojosugito (HM Publisher, 2026)
Background: The development of a broadly protective dengue virus (DENV) vaccine remains a paramount global health priority. Current tetravalent vaccines target the four DENV serotypes. However, intra-serotypic genetic variations, defined as genotypes, present a neglected immunological barrier. Evidence indicates that genotypic divergence critically impairs cross-neutralizing antibody responses, leaving vaccinated individuals vulnerable to circulating heterologous genotypes and severe antibody-dependent enhancement (ADE). This meta-analysis quantifies the impact of DENV genotypic variation on neutralizing antibody efficacy. Methods: A systematic review and meta-analysis adhering to PRISMA guidelines were conducted. Quantitative virological data were extracted from primary studies, focusing on neutralizing antibody titers against homologous versus heterologous DENV genotypes. A DerSimonian-Laird random-effects model calculated the pooled Standardized Mean Difference (SMD) and 95% Confidence Intervals (CI). Heterogeneity was addressed through subgroup analyses (by serotype and host species). A sensitivity analysis employing the Hartung-Knapp-Sidik-Jonkman (HKSJ) adjustment verified robustness. Risk of bias was evaluated utilizing RoB 2 and SYRCLE tools. Results: Ten controlled studies met the inclusion criteria. The pooled analysis revealed a severe, statistically significant reduction in neutralization capacity against heterologous genotypes compared to homologous strains, yielding an overall SMD of -1.52 (95% CI: -1.95 to -1.09, p < 0.001). High initial heterogeneity (I2 = 84.1%) was partially resolved by stratifying by serotype; the DENV-2 subgroup demonstrated the most profound neutralization deficit (SMD = -1.78, I2 = 42.5%). Sensitivity analyses confirmed the stability of the pooled effect. Conclusion: Vaccine-induced neutralizing responses are significantly attenuated against heterologous DENV genotypes. The prevailing serotype-level vaccine paradigm is insufficient for comprehensive global immunity. Next-generation vaccine designs must incorporate conserved, pan-genotypic epitopes to prevent intra-serotypic immune evasion and subsequent ADE-mediated severe disease.